Appropriating Public Private Partnership in Senior High School Program: A Socio-Cultural Approach to Policy Making - Peter G. Romerosa (Udayana Journal of Law and Culture, 2018)
The implementation of the Senior High School program in the Philippines illuminates the State’s response to the changing landscape of the global market economy. Its salient features focus on the additional two year-senior high school program which highlights the development of middle level skills for national development and global competitiveness. In order to concretize the implementation of the program, the State entered into collaboration with the private schools which is commonly known as Public Private Partnership (PPP). In this collaboration, the government provides the guidelines and financing while the private educational institutions provide the academic service. Framed from a socio-cultural approach to policy making in education, this study aimed to unpack a particular implementation of PPP of a private institution in an urban area, examine the institutional policies that were created in response to PPP, and interrogate the impacts of these policies on micro social processes. Using interviews and focus group discussions for methodology, the researcher drew narratives and insights from on-the-ground actors. Further, the investigation looked into how authorized policy actors (school administrators) and nonauthorized policy actors (teachers, parents, and students) are appropriating policies within the operational framework of the PPP in the implementation of the senior high school program. The results demonstrated that multi- layered appropriation and exercise of the agency were explicitly and implicitly deployed in diverse social spaces by actors as a pragmatic and creative response to the new educational arrangement. The paper provides a lens to further develop under-standing on how policy appropriation and production from the local context can inform institutional approaches in facilitating relevant student experience within the realm of PPP in education.